Analysis of Gender Equality Against Per Capita Income on Sumatra Island - Khairul Kamal; Raina Linda Sari; Wahyu Ario Pratomo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study analyzes the impact of gender equality on per capita income in the Sumatra region using a panel data approach with the Random Effects Model (REM) estimation method. The model yielded a coefficient of determination (R²) of 0.73825. In the context of the Sustainable Development Goals (SDGs), gender equality is considered a key element in promoting inclusive and sustainable economic growth. This study utilizes panel data from 2018 to 2023, covering seven main indicators: the Human Development Index (HDI), the Gender Development Index (GDI), the Gender Inequality Index (GII), the ratio of average years of schooling between males and females (RLS), the ratio of the productive age population between males and females (RUP), the ratio of labor force participation rate between males and females (RTPAK), and women's representation in parliament (PP). The analysis results indicate that the Human Development Index and the ratio of average years of schooling between males and females have a positive and significant effect on per capita income in the Sumatra region.